Festive Row of the Iconostasis of the Assumption Cathedral of the Big Tikhvin Monastery and Its Place in the Art of the Ivan the Terrible Era - Shalina, Irina A. (Actual Problems of Theory and History of Art, 2021)
The most significant in quality and quantity medieval ensemble preserved in the Russian Museum is the iconostasis of the Assumption Cathedral of the Tikhvin Monastery (ab. 60 icons), acquired as a result of the museum’s expeditionary activity in the 1950–60s. It included the Local, Deesis, Festive, Prophetic, and Forefather rows painted by masters of the 16th and 17th centuries. As it was established, the oldest part of the ensemble ended up in Tikhvin only in 1623. The monuments were received from the Voskresensky Derevyanitsky Monastery in Novgorod, where during the years of the Swedish occupation of the Konevets Island the iconostasis of the Church of the Nativity of the Virgin of the Konevets Monastery had been temporarily kept. The time and circumstances of its creation was determined by the document of 1554 informing about the restoration of the church decor after the fire at the expense of the royal treasury. The high level of artisanship of the Deesis, Festival, and Prophetic rows of the Konevets ensemble brought to Tikhvin makes it possible to associate its creation with the leading metropolitan workshop of the mid-16th century. Judging by the style of certain icons, the Novgorod icon painters also worked for that workshop. The Festive row is distinguished by the integrity of the design and the iconography of the icons included in it, and their artistic features find close parallels with the work of Moscow artists, primarily the festive icons of the iconostases of the upper chapels of the Annunciation Cathedral of the Moscow Kremlin (1560s). Both ensembles represent the leading trend of official art of the era of Ivan the Terrible. The reported study was funded by RFBR, project number 18-012-00512.